NGS identifies novel HLA-DQA1 and DPB1 associations with aplastic anemia in the Kazakhstani population - Turganbekova, Aida; Zhanzakova, Zhulduz; Kanabekova, Perizat; Baimukasheva, Dana; Saduakas, Zhazira; Khamitova, Didara; Abdrakhmanova, Saniya; Masalimov, Zhaksylyk; Almawi, Wassim Y. (Frontiers in Immunology, 2026)
BackgroundAplastic anemia (AA) is a rare but serious blood disorder defined by autoimmune-driven destruction of bone marrow stem and progenitor cells. HLA polymorphisms are AA risk factors, with population-specific associations influencing disease susceptibility, treatment response, and transplant outcomes. While the genetic pathways driving AA development remain incompletely elucidated, a link between HLA variants and AA predisposition has been documented across diverse ethnic groups, though not in Central Asian communities, particularly in Kazakhstan.ObjectiveWe investigated the relationship between HLA Class I and Class II alleles and the risk of AA in the Kazakhstani population using high-resolution NGS genotyping.MethodsThe study included 91 patients with AA and 250 unrelated controls selected from the national registry of hematopoietic stem cell donors. HLA class I (A/C/B) and class II (DRB1/DQA1/DQB1/DPB1) high-resolution genotyping was conducted using NGS. Statistical significance was assessed with chi-square tests.ResultsClass II alleles showed stronger associations with AA than Class I alleles. Novel HLA associations with strong effect sizes (ORs >69) were identified, including the first-ever reported associations between HLA-DQA1 alleles and AA susceptibility. DRB1*05:05:01, DRB1*01:02:01, DQA1*05:05:01, DQA1*03:03:01, DQA1*03:02:01, DQA1*01:04:01, DQB1*02:02:01, DPB1*02:01:02, and DPB1*104:01:01 were associated with a higher AA risk in the Kazakhstani population. In contrast, DRB1*07:01:01, DRB1*15:01:01, DQA1*03:01:01, DQA1*01:01:01, DQA1*05:01:01, DQB1*02:01:01, and DPB1*02:01:01 were linked with reduced risk. Among Class I alleles, only B*40:02:01 showed a weak association with increased AA risk (p = 0.042), markedly lower than the strong Class II effects.ConclusionsClass II alleles, including those within DQA1 and DPB1, are important genetic factors influencing AA susceptibility in Kazakhstan. It highlights the need for region-specific genetic profiling to improve disease risk assessment and guide therapeutic strategies.